Obstacles and Challenges in Implementing Authentic Assessment in Elementary Madrasah - Devi Radnasari; Fatonah , Siti (International Journal of Basic Educational Research, 2025)
This article discusses the implementation of authentic assessment in the context of Madrasah Ibtidaiyah, focusing on the obstacles faced by teachers and practical recommendations to overcome them. In the background of the study, it was stated that authentic assessment is a widely discussed approach to comprehensively assess students' abilities through real-life relevant tasks. However, its implementation in Madrasah Ibtidaiyah faces various obstacles, including lack of teacher understanding and skills and limited resources and institutional support. The research methodology uses a qualitative approach with a case study method at MIN 2 OKU TIMUR. Data were collected through in-depth interviews with teachers and participant observation in the classroom. The main results indicate structural, pedagogical, and technical obstacles in the implementation of authentic assessment, such as lack of institutional support, limited teacher knowledge and skills, and technological obstacles. Practical recommendations are formulated to overcome these obstacles, including increasing institutional support through facilities and intensive training for teachers, developing teacher skills through workshops and mentoring, and technical solutions such as providing adequate technology and developing a digital assessment system. In conclusion, this study highlights the importance of institutional support and teacher skill development in enhancing the effectiveness of authentic assessment in Madrasah Ibtidaiyah, while emphasizing the need for further investigation in a broader context and research on the use of technology in assessment.